183 DEVELOPING AND FACILITATING ONLINE INTERGENERATIONAL CAFÉS. (25th October 2022) - Tuohy, D; Cassidy, I; Carey, E; Graham, M; McCarthy, J; Murphy, J; Morrissey, K; Shanahan, J; Tuohy, T
Abstract: Background: Many older people throughout their lives will require nursing care, consequentially most nurses will care for older people during their career. It is important that older people and student nurses are provided with shared learning opportunities so that professional caring partnerships can be nurtured and realised for mutual benefit. Intergenerational projects offer opportunities for intergenerational learning. However, few projects explore student nurse-older person dyads and how these can be integrated within undergraduate pre-registration programmes. This paper describes the development and facilitation of online older person-student nurse intergenerational cafés. Methods: The project was managed by a design team comprising senior administration, lecturers in BSc Nursing programmes and a lecturer in Design for Health and Wellbeing. The 'world café' concept along with values of enablement and participation underpinned the design. The initiative was planned to align with a year three community care module. Regular online team meetings were held to agree the aims and outcomes for student nurse-older person cohorts, decide recruitment strategies, agree the process and format of facilitation. Older people were recruited through retirement, church, volunteer, social and sporting organisations, media and also using snowballing methods. Results: Both student nurse and older person cohorts were offered support on how to access and participate in the café. Participants attended one of three online cafés hosted through Microsoft Teams. Each café followed the same format: 1) Group meeting convened with all participants; 2) Breakout small group 'table' discussions with student nurse-older people participants and design team facilitation; 3) The café was reconvened to whole group meeting where feedback was collated to elicit shared learning. Conclusion: The initiative proved successful and there is merit in embedding intergenerational cafés into professionally accredited health care programmes. Through sharing life experiences and perspectives, intergenerational barriers can be reduced and new insights developed on person-centred gerontological care.